AN ANALYSIS OF STUDENTS’ CULTURE SHOCK IN LEARNING ENGLISH AT CENTRAL COURSE IN KAMPUNG INGGRIS PARE – KEDIRI - Kadnawi (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
In this era of globalization, English Language is essential for our daily life,and also english is the language that has always been used to communicate in every country, in actuality the second most spoken language worldwide. Culture shock refers to the impact of moving from a familiar culture to one that is unfamiliar. This impact includes the anxiety and feelings (such as surprise, disorientation, uncertainty, and confusion) felt when a person must adapt to a different and unknown cultural or social environment. This research using a qualitative method (field research), this research is designed to analyze what students’culture shock that they feel when learning english at central course in kampung inggris pare kediri. Based on the findings of research and discussion, the students feel enjoy and fun in learning English. Then some of students find the culture shock during they study english which has different culture that make them unfamiliar, but there are also students who have poor social cultural adaption. Culture shock is very influential in the social cultural adaptation of students. The way a child lives in their old environment will also affect the social and cultural adaptation of their new environment.